2014
DOI: 10.1186/1748-717x-9-115
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated partial breast irradiation in the elderly: 5-year results of high-dose rate multi-catheter brachytherapy

Abstract: ObjectiveTo evaluate clinical outcome after accelerated partial breast irradiation (APBI) in the elderly after high-dose-rate interstitial multi-catheter brachytherapy (HIBT).Methods and materialsBetween 2005 and 2013, 70 patients underwent APBI using HIBT. Catheter implant was performed intra or post-operatively (referred patients) after lumpectomy and axillary sentinel lymph node dissection. Once the pathological results confirmed the indication of APBI, planification CT-scan was performed to deliver 34 Gy/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 40 publications
(57 reference statements)
4
19
0
3
Order By: Relevance
“…Two trials of intraoperative radiotherapy reported higher rates of LR compared with conventional WBI (35,36). The GEC-ESTRO APBI phase III compared WBI versus APBI for selected primary early-stage breast cancer (low and intermediaterisk groups) (37) and the 5-year LRFS was 98.6%, which is similar to our 5-year LRFS of 98.1% previously described (19). With a 12-year median follow-up, Polgar et al (38) reported a 5-year LR rate of 4.7% with 77% of good/excellent cosmetic results.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Two trials of intraoperative radiotherapy reported higher rates of LR compared with conventional WBI (35,36). The GEC-ESTRO APBI phase III compared WBI versus APBI for selected primary early-stage breast cancer (low and intermediaterisk groups) (37) and the 5-year LRFS was 98.6%, which is similar to our 5-year LRFS of 98.1% previously described (19). With a 12-year median follow-up, Polgar et al (38) reported a 5-year LR rate of 4.7% with 77% of good/excellent cosmetic results.…”
Section: Discussionsupporting
confidence: 81%
“…We have previously reported the 5-year clinical outcome of a cohort of elderly women treated with APBI based on a high-dose rate interstitial multicatheter brachytherapy (HIBT), but a longer follow-up was needed to assess the consistency of our results. The aim of this report was to update the clinical outcome after APBI in our previously published cohort and discuss prognostic factors (19).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment decisions in elderly cancer patients need to focus not only on local control and overall survival but primarily on quality of life. Sumodhee et al [45 ]and Genebes et al [46] demonstrated in their studies that MIB can perfectly apply sufficient local irradiation with maximum preservation of OAR in a very short treatment period with excellent local control and low acute and chronic side effects. This could be an ideal alternative for elderly breast cancer patients, representing a compromise between omitting radiotherapy and a whole course of WBI.…”
Section: Role Of Brachytherapy In Accelerated Partial Breast Irradiationmentioning
confidence: 99%
“…The cosmetic evaluation was based on the standards set forth in the Harvard criteria, which consisted of a four tiered grading system: excellent, good, fair, and poor. [3] Late toxicity of the skin and subcutaneous tissue was scored according to the Radiation Therapy Oncology Group (RTOG)/European Organization for Research and Treatment of Cancer late radiation morbidity scoring scheme. [4,6] …”
Section: Methodsmentioning
confidence: 99%
“…This translates into 15 years breast cancer mortality reduction by 5%. [3] BT is used as an adjuvant therapy in BCT either alone or combined with external radiotherapy to boost the primary site provided the facility and expertise is available at the treating centre. Many centers use RT and alternative boost technique like IMRT, Electron beam, coned downed photon, TARGIT or nonradiation local treatment like cryotherapy,RFA ablation, focussed US etc.…”
Section: Introductionmentioning
confidence: 99%